Simultaneous enantioseparation and simulation studies of atenolol, metoprolol and propranolol on Chiralpak® IG column using supercritical fluid chromatography - Pranav A. Pandya; Priyanka A. Shah; Pranav S. Shrivastav (Elsevier, 2021)
Enantioseparation of three β-blockers, i.e., atenolol, metoprolol and propranolol, was studied on amylose tris(3-chloro-5-methylphenylcarbamate) immobilized chiral stationary phase using supercritical fluid chromatography (SFC). The effect of organic modifiers (methanol, isopropanol and their mixture), column temperature and back pressure on chiral separation of β-blockers was evaluated. Optimum chromatographic separation with respect to resolution, retention, and analysis time was achieved using a mixture of CO2 and 0.1% isopropyl amine in isopropanol: methanol (50:50, V/V), in 75:25 (V/V) ratio. Under the optimized conditions, the resolution factors (Rs) and separation factors (α) were greater than 3.0 and 1.5, respectively. Further, with increase in temperature (25-45 °C) and pressure (100-150 bars) there was corresponding decrease in retention factors (k), α and Rs. However, a reverse trend (α and Rs) was observed for atenolol with increase in temperature. The thermodynamic data from van't Hoff plots revealed that the enantioseparation was enthalpy driven for metoprolol and propranolol while entropy driven for atenolol. To understand the mechanism of chiral recognition and the elution behavior of the enantiomers, molecular docking studies were performed. The binding energies obtained from simulation studies were in good agreement with the elution order found experimentally and also with the free energy values. The method was validated in the concentration range of 0.5-10 μg/mL for all the enantiomers. The limit of detection and limit of quantitation ranged from 0.126 to 0.137 μg/mL and 0.376-0.414 μg/mL, respectively. The method was used successfully to analyze these drugs in pharmaceutical preparations.